REFERENCE BOOKS IN THE HISTORY OF DENTAL MEDICINE PIERRE FAUCHARD AND HIS HANDBOOK OF THE TEETH (1728) (II) - Irina Croitoru (Romanian Journal of Oral Rehabilitation, 2014)
The journey into the world of books about the history of dental medicine, proposed by our paragraph, debuted in the first number of the review in 2014 with the book of Pierre Fauchard (1679-1761), Le Chirurgien dentiste ou Traité des dents, which had the first edition in 1728, the second in 1746 and the third in 1786. In the last article our journey was about the life, the personality, the current international appreciation and the structure of the first volume (partly compiled). We suggest the reader to stop now on the content of the second volume, work with an original character, the creativity and the professional passion of the Parisian doctor taking place here. The rigorous, precise, scientific language, reveals the value a universe of knowledge of the anatomy of the mouth and dentition, throughout its evolution, its encountered pathology, its interventions of surgical nature, descriptions of the surgical techniques used, but especially descriptions as precisely as possible of the medical instruments used in the dental surgery, mostly invented and designed by the author.